Endoscopic treatment of intraluminal duodenal (“windsock”) diverticulum: varying techniques from five cases - Law, R.; Topazian, M.; Baron, T. H. (Endoscopy, 2012)
The optimal endoscopic approach to intraluminal duodenal diverticulum (IDD) has not been established. We report on our experience of endoscopic resection of symptomatic IDD in five patients (three men, two women; mean age 37 years) who were treated between August 2004 and April 2012. Four patients underwent endoscopic diverticulectomy using a standard polypectomy snare. Following diverticulectomy, the remaining duodenal septum was incised using a needle-knife in two patients. The fifth patient underwent endoscopic diverticulotomy using a needle-knife. In four cases the IDD was resected and reviewed histologically and demonstrated substantial vascularity. All patients developed clinically significant, post-procedural bleeding, which was managed endoscopically. Endoscopic management of symptomatic IDD can be achieved using various approaches. Post-procedural bleeding appears to be a common adverse event, but this complication can be managed endoscopically.